Living a Happy Life According to Buddhism: Living a Happy Life According to Buddhism - yodboon, pornpirom (Journal of MCU Buddhasothorn Review, 2022)
Abstract Living have both of physical and mental happiness or suffering. With these causes, living is for only happiness according to Buddhism how we can do. Exactly, this article would present the meaning and importance of happiness in Buddhism by measure of happiness’s level, because the procedures could assign that each person could have some level of happiness. With this measure, we could understand that we have the procedures and theories to create the happiness in own our lives. the types and methods of happiness were divided in both worldly and morally ways. Living in both of them was for creating the life to have the happiness and value.